Real-time PCR for diagnosing and monitoring treatment effect of Strongyloides stercoralis infection in a non-endemic setting - Wammes, Linda J.; van Asten, Suzanne A. V.; van Lieshout, Lisette; Wessels, Els; Verweij, Jaco J. (Frontiers in Parasitology, 2023)
Word count: 211 Introduction The laboratory diagnosis of Strongyloides stercoralis is notoriously difficult. Microscopic diagnosis, even using concentration techniques and repeated sampling, is known to lack sensitivity. Serology depending on the type of test used have shown adequate sensitivity but specificity is generally low. In the present study the performance of S. stercoralis real-time PCR as a routine diagnostic test is evaluated in two different non-endemic settings. Methods Strongyloides stercoralis real-time PCR, serology, and microscopy results with available clinical and anamnestic data were extracted from the laboratory information management systems between August 2005 and December 2022. Results A total of 19179 Strongyloides stercoralis PCR results were retrieved in which in 149 specimens from 103 patients S. stercoralisspecific DNA was detected. Microscopy revealed S. stercoralis larvae in 19 of 36 (53%) PCR positive patients. Whereas serology tested positive in 70 of 74 (94.6%) of all available serum samples of S. stercoralis PCR positive patients and in 61 of 63 (96.8%) when limited to serology results within 6 weeks around the primary PCR-positive specimen. In 79% (38 of 48 patients) the first follow-up feces sample tested PCR negative. Discussion Strongyloides stercoralis real-time PCR showed a valuable diagnostic tool for the detecting and monitoring of S. stercoralis infections and detected additional cases compared to microscopy and serology.